ALTERNATIVE PARKING NEED FOR THE CHANDRA SUPER STORE TANJUNG KARANG PARKING AREA - A. R. Indra Tjahjani Tjahjani; atika dalima (Jurnal Infrastruktur, 2021)
Bandar Lampung is the largest city in Lampung province and the third most populous city on Sumatra island. The population of this city is increasing every year. Since Bandar Lampung becomes a business center, it causes a transportation problem. One of which is parking in a public area like a mall. The purpose of this study was to find out and analyze the parking characteristics in Chandra Super Store Tanjung Karang and to analyze the capacity and parking spaces needs in Chandra Super Store Tanjung Karang. The method in this study uses secondary data consisting of data in and out of parking vehicles. From these data, an analysis is carried out to obtain the accumulation of parking, parking volume, parking duration, parking turnover rate, parking capacity, parking index, and parking requirements. The results of this study are maximum accumulation parking for cars is 592 vehicles, while motorcycles are 676 vehicles, with the average are 536 for cars and 580 for motorcycles. For maximum daily volume, the results are 1803 for cars and 1764 for motorcycles, with daily average are1429 for cars and 1495 for motorcycles. For the average duration of cars and motorcycles are 3,6 and 3,7 hours. The result for maximum car parking turnover is 4,145 with the average is 3,284. While for motorcycle is 3,285 with the average is 3. The average for parking index is 1,215 for cars and 1,131 for motorcycles. The maximum capacity of parking is 498 PSU while the needs are 572 PSU, So it can be concluded that the existing parking capacity is not able to meet the needs. It can be concluded that the existing parking capacity is not able to meet the needs. As an alternative to choosing the parking facility at Chandra Super Store, the Hydraulic Automatic Parking system.